2000
DOI: 10.1096/fj.00-0250com
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin‐1 expression by tumor cells promotes tumor angiogenesis and progression

Abstract: Neuropilin-1 (NRP1) is a VEGF(165) and semaphorin receptor expressed by vascular endothelial cells (EC) and tumor cells. The function of NRP1 in tumor cells is unknown. NRP1 was overexpressed in Dunning rat prostate carcinoma AT2.1 cells using a tetracycline-inducible promoter. Concomitant with increased NRP1 expression in response to a tetracycline homologue, doxycycline (Dox), basal cell motility, and VEGF(165) binding were increased three- to fourfold in vitro. However, induction of NRP1 did not affect tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
250
3
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(268 citation statements)
references
References 48 publications
11
250
3
4
Order By: Relevance
“…Whether the protumorigenic effect of combined HH‐IL6 signaling is directly mediated by the HH‐IL6 targets EDN2, PLAT and NRP1 requires further functional studies. In this context, it is noteworthy that PLAT and NRP1 play a well‐documented role in angiogenesis, in line with previous reports about a putative angiogenic function of IL6 in BCC 45, 46, 47. However, as we did not detect a decrease in CD31 + endothelial cells in Il6ra‐deficient mouse BCC (data not shown), it appears rather unlikely that HH‐IL6 signal integration drives BCC growth by supporting tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Whether the protumorigenic effect of combined HH‐IL6 signaling is directly mediated by the HH‐IL6 targets EDN2, PLAT and NRP1 requires further functional studies. In this context, it is noteworthy that PLAT and NRP1 play a well‐documented role in angiogenesis, in line with previous reports about a putative angiogenic function of IL6 in BCC 45, 46, 47. However, as we did not detect a decrease in CD31 + endothelial cells in Il6ra‐deficient mouse BCC (data not shown), it appears rather unlikely that HH‐IL6 signal integration drives BCC growth by supporting tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…In a prostate cancer model, transfection of NRP-1 increased VEGF 165 binding, basal cell motility, and tumour size in vivo (Miao et al, 2000), suggesting that the receptor functions in a VEGF-dependent fashion to enhance tumorigenicity. However, the survival effects demonstrated in our study occurred in two cell lines that do not express VEGFR-2, although they do express VEGFR-1.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to its role as a Sema3A receptor, neuropilin-1 is a co-receptor for a specific isoform of VEGF165 and guides endothelial cell migration during vascular morphogenesis (Soker et al, 1998;Lee et al, 2002). The role of neuropilin-1 in tumors has been mostly studied in the context of its interaction with VEGF165 and related to tumor angiogenesis and tumor cell survival (Miao et al, 2000;Bachelder et al, 2001). A recent study suggested that neuropilin-1 contributes to tumor progression by potentiating the activity of hepatocyte growth factor as well (Hu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%